Adsorption of zinc ions on bone char using helical coil-packed bed columns and its mass transfer modeling. Issue 51 (1st November 2016) - Moreno-Pérez, J.; Bonilla-Petriciolet, A.; Rojas-Mayorga, C.K.; Mendoza-Castillo, D.I.; Mascia, M.; Errico, M.
Abstract: This study reports the assessment of helical coil-packed bed columns for Zn 2+ adsorption on bone char. Zn 2+ adsorption breakthrough curves have been obtained using helical coil columns with different characteristics and a comparison has been conducted with respect to the results of straight fixed-bed columns. Results showed that the helical coil adsorption columns may offer an equivalent removal performance than that obtained for the traditional packed bed columns but using a compact structure. However, the coil diameter, number of turns, and feed flow appear to be crucial parameters for obtaining the best performance in this packed-bed geometry. A mass transfer model for a mobile fluid flowing through a porous media was used for fitting and predicting the Zn 2+ breakthrough curves in helical coil bed columns. Results of adsorbent physicochemical characterization showed that Zn 2+ adsorption on bone char can be attributed to an ion-exchange mechanism. In summary, helical coil columns appear to be a feasible configuration for large-scale adsorption systems with high flow rates where a significant reduction on purification system size can be obtained without compromising the adsorbent performance.